Peranan Pendidikan Agama Islam dalam Pencegahan Pelecehan Seksual Online di Kalangan Mahasiswa - Munawir Pasaribu (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The development of education is currently being tested with various cases and problems that befall, not only curriculum problems, and infrastructure but also now overwritten with problems in actions such as sexual harassment experienced by students. The harassment that occurred was in the form of online and some in person. Some of this sexual harassment is done not by outside parties but can happen by people close to the victim, such as girlfriends and classmates. The role of Islamic religious education must have a big role in solving this problem, how can religious education actually be a control in doing something so that the measure is right and wrong or good and bad. This study aims to find information on how the actual role of Islamic religious education in suppressing sexual harassment both online and directly, then whether any of the students studied in this study experienced or were perpetrators of online sexual harassment, who the perpetrators were, and what types of online sexual harassment were received. by the victim. In addition, the purpose of this research is to provide anticipation and lessons to reduce the occurrence of online sexual harassment. This study involved 232 students at the Muhammadiyah University of North Sumatra from various majors and different residential areas. This research method uses mixed research, where the approach in the research is quantitative by analyzing numbers, and in the qualitative approach uses descriptive analysis. Searching for information about the things being researched by researchers uses a questionnaire in the form of a google form, to strengthen the results of the answers from the respondents, the researchers also conduct limited questions and are bound to the respondents. As for testing the validity of the data, the researchers used Melles and Huberman. The results obtained indicate that the provision of Islamic religious education materials has a very high role in overcoming or controlling students so that they are not involved as perpetrators of online or offline sexual harassment. The types of sexual harassment experienced by students are starting from using social media that is not well controlled, the harassment they get is in the form of sending pornographic photos, and pornographic videos and asking for nude photos and videos.